DETERMINAN AGRESIVITAS PAJAK : PENGARUH CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN DI INDONESIA - Fransiska, Christina; Diarsyad, Muhammad Ichsan (ITB AAS INDONESIA, 2024)
This research aims to examine the financial factors that influence Tax Aggressiveness with Corporate Social Responsibility Disclosure as a Moderating Variable in Manufacturing Companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The research method used in this research is quantitative and uses secondary data collection techniques in the form of financial reports and Corporate Social Responsibility Disclosure reports. The sample in this study was selected using a purposive sampling method and there were 12 companies that met the sample criteria. The results of the research show that Capital Intensity has a significant effect on Tax Aggressiveness, while Company Size and Leverage have no effect on Tax Aggressiveness. The results of the moderation analysis show that Corporate Social Responsibility is able to strengthen Capital Intensity and Leverage on Tax Aggressiveness, while the influence of Company Size on Tax Aggressiveness cannot be moderated by Corporate Social Responsibility. This research contributes to companies in Indonesia as a consideration for management in carrying out Corporate Social Responsibility and its relationship with the influence of financial factors on corporate tax aggressiveness.